Dietary and nutraceutical interventions as an adjunct to non-surgical periodontal therapy: a systematic review - Wölber, Johan; Reichenbächer, Katharina; Groß, Tara; Vach, Kirstin; Ratka-Krüger, Petra; Bartha, Valentin (Nutrients, 2023)
The aim of this study was to conduct a systematic literature review on the influence of dietary and nutraceutical interventions as an adjunct to non-surgical periodontal therapy (NSPT). A literature search for randomized, controlled clinical trials (RCTs) was performed in PubMed, the Cochrane Library, and the Web of Science. Trial inclusion criteria included the application of a defined nutritional intervention (food, beverages, or supplements) adjunctive to NSPT compared to NSPT alone with at least one measured periodontal parameter (pocket probing depths (PPD) or clinical attachment level (CAL)). Of 462 search results, 20 clinical trials relating to periodontitis and nutritional interventions were identified, of which, in total, 14 studies could be included. Eleven studies examined supplements containing lycopene, folate, chicory extract, juice powder, micronutrients and plant extracts, omega-3 fatty acids, vitamin E, or vitamin D. Three studies examined food-based interventions (kiwifruit, green or oolong tea). Due to limited information on within-group differences in the studies, results were descriptively analyzed. A significant positive effect on periodontal parameters (PPD, bleeding on probing) was found for vitamin E, chicory extract, juice powder, green tea, and oolong tea. Heterogeneous effects were found for lycopene, folate, omega-3 fatty acids, and vitamin D. No effects on PPD were found for adjunct kiwifruit (in combination with NSPT). Risk of bias via RoB2 revealed a low risk of bias with some concerns. There was a high heterogeneity in the type of nutritional interventions. The adjunctive use of various supplements and green/oolong tea led to positive and significant effects of the nutritional interventions on clinical periodontal outcome parameters. In the context of non-surgical periodontal therapy, an adjunctive intake of micronutrients, omega-3 fatty acids, green/oolong tea, and polyphenols and flavonoids could be beneficial. Long-term clinical studies with full data reports (especially within-group differences) are needed for conducting a meta-analysis.